Health-Oriented Retail Strategies: How the Perceived Accessibility of Nutri-Level Labels Influences Customer Attitudes, Satisfaction, Repurchase Intentions, and Loyalty: Strategi Ritel Berorientasi Kesehatan: Bagaimana Persepsi Aksesibilitas Label Tingkat Nutrisi Mempengaruhi Sikap Pelanggan, Kepuasan, Niat Pembelian Ulang, dan Loyalitas - Wildan Avian Pratama; Tita Alfaricha; Ardy Wibowo (Universitas Muhammadiyah Sidoarjo, 2026)
The implementation of Nutri-Level Labels (NLL) is promoted more and more as a policy tool to support healthier consumer choices in Indonesia; however, the empirical evidence regarding the effects of the accessibility of these labels on customer behavior in retail environments is scarce. This study is aimed at examining the influence of customer perceptions of accessibility of Nutrition Level Labels to customer attitudes, customer satisfaction, retail customer loyalty, and customer re-purchase intention. Using a quantitative approach, data were gathered from 320 respondents using purposive sampling through a structured survey and analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM). The results suggest that the academic attitude and satisfaction, customer loyalty, and commitment to purchase of customers have a significant positive impact on customer attitudes and satisfaction because of the perceived accessibility of nutrition labels. Furthermore, customer attitudes as well as customer satisfaction are capable of mediating the connection between nutrition label accessibility and customer loyalty and repurchase intentions at retail. These findings suggest that when retail stores make it easy for visitors to find easily accessible nutrition labels, it can shape customer behavior. This study points to the importance of retail strategies in the organization of health-oriented stores by providing store layouts with user-centered and product nutrition-level information and offers practical implications for retailers and policy makers in the development of health-oriented retail environments.